Optimising the tension of an autologous fascia pubovaginal sling to minimize retentive complications. Issue 5 (18th April 2019) - Preece, Patrick D.; Chan, Garson; O'Connell, Helen E.; Gani, Johan
Abstract: Aim: To determine the optimal degree of pubovaginal slings (PVS) tension, measured by lax sling dimensions to minimize the risk of urinary retention. Methods: This prospective study analyzed female patients undergoing PVS for stress urinary incontinence (SUI) by two surgeons over 24 months from January 2016. Intra‐operative measurements of lax sling dimensions tented over rectus fascia were recorded. Logistic regression was used to analyse the likelihood of urinary retention (more than 3 months of intermittent self‐catheterisation (ISC) or surgical revision) for given PVS dimensions. The secondary analysis assessed for an association between PVS measurements and persistent SUI. Results: Fifty‐one patients were recruited with a median age of 53 (34‐78) and follow‐up of 11 (3‐20) months. All but one patient reported improvement of SUI. Ten (19.6%) patients developed postoperative urinary retention. Five (9.8%) resolved after a temporary period of ISC. The other five (9.8%) required ongoing ISC or sling division. A strong association existed between short sling height and prolonged urinary retention ( P  = 0.00). Receiver operating characteristic (ROC) curve analysis showed a sling height of 40 mm had a sensitivity of 100% and specificity of 51% for retentive complications (area under curve [AUC]  = 0.90). Lax sling height up to 60 mm was not associated with persistent SUI. Conclusions: Stretching the sling suspension sutures at least 40 mm above the rectus fascia was associated with a lower risk of urinary retention than less than 40 mm. This simple technique would appear to be worth evaluating in a larger sample. A looser sling did not compromise the cure of SUI at a mean follow‐up of 11 months.